The Effect of Temperature, Potato Varieties, and the Origin of Cyst on the Reproductive Biology of Globodera rostochiensis - Nurjanah Nurjanah; Y. Andi Trisyono; Siwi Indarti; Sedyo Hartono (Universitas Gadjah Mada, 2016)
Potato cyst nematode (Globodera rostochiensis [Wollenweber] Behrens) is a nematode species of worldwide regulatory concern. This nematode caused serious economic of potato losses in Indonesia. This research studied by factorial designed to evaluated the effect of temperature (10, 20, and 30ºC), potato varieties (`Granola´, `Margahayu´, and `Cipanas´), and origin of cyst (West, Central, and East Java) on reproductive biology of G. rostochiensis in the growth chamber. The research was conducted by observed of produced the new cyst number, reproduction fitness, survival, fecundity, and multiplication of G. rostochiensis. The result showed that all of the potato varieties were infected by G. rostochiensis when they were grown at the temperature ranging of 20 and 30ºC but not at 10ºC. The optimum temperature for maximum number of cysts with the highest reproduction factor, survival, fecundity and multiplication rate for all populations was 20ºC. The origin of cyst did not have any effect on the reproductive rate. The temperature of 20ºC provided is best environment for the life of G. rostochiensis on Granola. INTISARINematoda sista kentang (Globodera rostochiensis [Wollenweber] Behrens) adalah spesies nematoda yang mendapatkan perhatian khusus di seluruh dunia. G. rostochiensis menyebabkan kerugian ekonomi yang serius pada pertanaman kentang di Indonesia. Penelitian ini menguji pengaruh perbedaan suhu (10, 20, dan 30ºC), varietas kentang (Granola, Cipanas, dan Margahayu), dan asal sista (Jawa Barat, Jawa Tengah, dan Jawa Timur) terhadap biologi reproduksi G. rostochiensis di growth chamber menggunakan rancangan acak lengkap faktorial. Pengamatan dilakukan terhadap jumlah sista baru, kemampuan reproduksi, daya tahan hidup, keperidian dan multiplikasi G. rostochiensis. Seluruh varietas kentang yang diuji terserang G. rostochiensis pada suhu 20 dan 30ºC kecuali pada suhu 10ºC. Kisaran suhu optimum untuk memperoleh jumlah sista baru yang maksimum dengan kemampuan reproduksi, daya tahan hidup, keperidian dan multiplikasi untuk semua populasi adalah 20ºC. Asal sista tidak berpengaruh terhadap biologi reproduksi yang diteliti. Kentang varietas Granola yang ditanam pada suhu 20ºC merupakan inang yang sesuai untuk kehidupan G. rostochiensis.